2020
DOI: 10.1117/1.jrs.14.026518
|View full text |Cite
|
Sign up to set email alerts
|

Learning synthetic aperture radar image despeckling without clean data

Abstract: Speckle noise can reduce the image quality of synthetic aperture radar (SAR) and make interpretation more difficult. Existing SAR image despeckling convolutional neural networks require quantities of noisy-clean image pairs. However, obtaining clean SAR images is very difficult. Because continuous convolution and pooling operations result in losing many informational details while extracting the deep features of the SAR image, the quality of recovered clean images becomes worse. Therefore, we propose a despeck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 48 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Those authors have argued that because the network is applied on US images, investigating the semantic information of neighboring video frames and 3D DNN models is important. Other authors have reported better processing times as well [26,27].…”
Section: Related Workmentioning
confidence: 80%
See 1 more Smart Citation
“…Those authors have argued that because the network is applied on US images, investigating the semantic information of neighboring video frames and 3D DNN models is important. Other authors have reported better processing times as well [26,27].…”
Section: Related Workmentioning
confidence: 80%
“…Another study which deals with speckle noise reduction in optical coherence tomography is [26]. The study introduces a novel self-supervised denoising approach, Sub2Full (S2F), for enhancing image quality in visible light optical coherence tomography (vis-OCT) without the need for clean data.…”
Section: Related Workmentioning
confidence: 99%
“…Different observations of the same land area cannot be deemed fully stationary, as the land feature is constantly changing. Addressing this problem, some researchers try to construct the image pairs by using synthesized speckled images [14,32,33], either directly for network training [32,33] or as an initial process [14] to evaluate and compensate for the change that occurs between multi-temporal images acquired over the same area. The training process using synthesized noisy images may inevitably bring in the domain gap.…”
Section: Related Workmentioning
confidence: 99%
“…It uses an architecture called Generative Adversarial Network (GAN). However, due to the high computation cost, these are generally applied for low-resolution images, such as in target recognition [19,20], or in a limited scene understanding, such as reducing speckle filters [21,22]. Another promising form of adding synthetic data for SAR is by using simulations.…”
Section: Introductionmentioning
confidence: 99%